To Arms! : colonial authors and the fiction of invasion 1890-1914 - Bulfin, Ailise (Trinity College (Dublin, Ireland). School of English, 2014)
In 1909 P. G. Wodehouse penned a comic novella The Swoop! which saw Britain saved from the simultaneous invasion of nine foreign armies by a boy scout named Clarence Chugwater. Wodehouse’s ludicrous plot, which featured invading armies not just from Britain’s imperial rivals like Germany and Russia, but also from unlikely nations like Switzerland, Monaco, Morocco and Somaliland, was a satirical take on an alarmist body of popular fiction that burgeoned in the period between 1890 and the beginning of World War I as international relations deteriorated globally. Within this body of work, popular authors proffered endless versions of expected war between the European imperial powers which frequently culminated in the invasion of Britain, the small island centre of the world’s then-largest empire.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin